Task solving as the basis of mathematical preparation of future engineers - Oleksenko, Viacheslav Mykhaylovych (Національний технічний університет "Харківський політехнічний інститут", 2019)
The results of the study of the problem of solving mathematical tasks in the preparation of future engineers are revealed. The urgency and importance of the topic is substantiated by the need of Ukrainian enterprises in qualified specialists of engineering specialties and the need of the society to ensure high quality of education. An approach to task solving in higher mathematics is theoretically developed. The peculiarities of its practical implementa-tion are clarified. Guidelines and steps for solving problems are explained. Rules for verifying resolved tasks are produced. The errors that future engi-neers make when solving tasks are classified. The necessity of making changes to the higher mathematics syllabus at the National Technical University "Kharkiv Polytechnic Institute" and the introduction of laboratory works using Mathcad, Mathlab, Scilab etc. are substantiated.

Статтю присвячено найголовнішому аспекту математичної підготовки майбутніх інженерів – розв’язуванню задач. Теоретично розроблено підхід до розв’язування задач з вищої математики. Розкрито особливості його практичної реалізації. Виявлено методичні рекомендації та етапи розв’язування задач. Висвітлено правила перевірки розв’язаних задач. Класифіковано помилки, яких припускаються майбутні інженери під час розв’язання задач. Досліджено структуру практичного заняття для ефективного вирішення поставленої проблеми. Рекомендовано схему самоаналізу викладачем проведеного заняття. Підтверджено високий результат розв’язання математичних задач на студактивних заняттях.
Розв’язування задач як основа математичної підготовки майбутніх інженерів
Keywords: higher mathematics; вища математика